Loss of function Cbl-c mutations in solid tumors - Daniels, Silvano Rakeem (PLoS One, 2019)
Receptor Tyrosine Kinase (RTK) signaling is essential for normal biological processes and disruption of this regulation can lead to tumor initiation and progression. Cbl proteins (Cbl, Cbl-b and Cbl-c) are a family of RING finger (RF) ubiquitin ligases that negatively regulate a variety of RTKs, including EGFR, MET, and RET. Recent studies have identified Cbl mutations associated with human myeloid neoplasias in approximately 5% of the cases. Cbl-c is the most recently identified human Cbl protein and is expressed exclusively in epithelial cells. We identified a novel cDNA that was isolated from a mouse mammary cancer from the C3(1) Large T Antigen transgenic model. This mutant cDNA encodes a protein that has a deletion in the RF domain of Cbl-c, thereby resembling known Cbl family mutations associated with myeoloid neoplasias. Genomic analysis of both parental and transgenic lines shows no evidence of germline mutation indicating that this mutation is likely a somatic mutation. The mutant protein enhances transformation of NIH 3T3 cells when expressed in combination with SV40 Large T antigen. Together these data are consistent with a second hit mutation. In overexpression studies, this mutant Cbl-c protein fails to mediate ubiquitination of activated EGFR and acts in a dominant negative fashion to prevent ubiquitination and downregulation of the activated EGFR by wild type Cbl proteins. Mechanistically, the mutant Cbl-c binds to the EGFR and prevents recruitment of the wild type Cbl protein. Furthermore, data mining reveals Cbl-c mutations associated with solid tumors in humans. Subsequent cell-based analysis demonstrates a similar loss of E3 function and dominant negative effects for one of these human mutations. These data suggest that like Cbl mutations in myeloid neoplasms, loss of Cbl-c function may contribute to the pathogenesis of solid tumors in murine models and in humans.